Riesgos en la comercialización de juegos de apuestas permanentes - chance en la empresa red de servicios de occidente S.A - Arboleda Echeverry, Danny Estrella; Pino Asprilla, Fairy Andrea; Martinez Blandon, Indira Vanessa (Universidad Antonio Nariño, 2022)
Taking into account the boom that has developed in recent years in the commercialization of Permanent Betting - chance in the department of Chocó and the inherent risks to which the company Red de Servicios de occidente S. A is exposed, due to the type The objective of this article is to determine the methodological approach of internal control, through a matrix which shows the most significant risks and the possible causes that generate them, based on internal policies. established by the company in the applicability of internal control through the MECI model, which seeks to achieve the corporate objectives of companies or entities and with the guidelines of the NTC ISO 31000 standard for risk management.